Technical Progress and Endogenous Growth: An Econometric Analysis Using Panel Data on the MENA Region - El Hajoui, Yassine; El Baouchari, Nabil; Ez-Zetouni, Adil (European Scientific Journal, ESJ, 2024)
From the dawn of the Christian era until the Industrial Revolution, the standard of living saw little to no change and remained relatively stable during this period. However, since the Industrial Revolution, living standards have experienced sustained growth up to the present day. The Solow model attributes this growth to technical progress, but where does this progress come from? To truly understand economic growth, we must therefore go beyond the Solow model and attempt to explain technical progress itself. The objective of this work is to identify and specify the factors that may explain technical progress (in other words, what causes growth in A (PGF)?). To this end, initially, we relied on a set of theoretical works ( (Romer, 1990; Lucas, 1988; Barro, 1990; Aghion, Blundell, Griffith, Howitt, & Prantl, 2009), among others) which led us to a set of recommendations. Therefore, in a second step, we proceed to an empirical analysis using panel data to test the significance of the impact of this set of recommendations on technical progress in the Middle East and North Africa (MENA) region. Our econometric results show that there is still much to be done in the MENA region to catch up with the United States, Sweeden, Switzerland, Japan, Germany or France: the establishment of a research and innovation system based on the needs of economic and social development, an increase in the budget allocated to research, massive investment by the private sector in universities, the strengthening and creation of institutions, etc.